Were COVID and the Great Recession Well-Being Reducing? - David G. Blanchflower; Alex Bryson (Institute of Labor Economics (IZA), 2023)
Using micro-data on six surveys – the Gallup World Poll 2005-2023, the U.S. Behavioral Risk Factor Surveillance System, 1993-2022, Eurobarometer 1991-2022, the UK Covid Social Survey Panel, 2020-2022, the European Social Survey 2002-2020 and the IPSOS Happiness Survey 2018-2023 – we show individuals' reports of subjective wellbeing in Europe did decline in the Great Recession of 2008/9 and during the Covid pandemic of 2020-2021 on most measures and on four bordering countries to Ukraine after the Russian invasion in 2022. However, the movements are not large and are not apparent everywhere. We also used data from the European Commission's Business and Consumer Surveys on people's expectations of life in general, their financial situation and the economic and employment situation in the country, all of which dropped markedly in the Great Recession and during Covid, but bounced back quickly, as did firms' expectations of the economy and the labor market. Neither the annual data from the United Nation's Humasn Development Index (HDI) nor data used in the World Happiness Report from the Gallup World Poll shifted much in response to negative shocks. The HDI has been rising in the last decade or so reflecting overall improvements in economic and social wellbeing, captured in part by real earnings growth, although it fell slightly after 2020 as life expectancy dipped. This secular improvement is mirrored in life satisfaction which has been rising in the last decade. However, so too have negative affect in Europe and despair in the United States.
Keywords: I31; 330; subjective wellbeing; life satisfaction; expectations; Human Development Index; Great Recession; COVID-19